Programme outcomes assessment in OBE implementation: On-line evaluation system/ Asmidar Alias ...[et al.] - Alias, Asmidar; Hashim, Norhafizah; Md Raus, Mohd Ikhsan; Mohamad Bhkari, Norshariza; Arifin, Kamisah (2009)
The move towards Outcome Based Education (OBE) approach for the diploma programmes at the Faculty of Civil Engineering for the whole system of Universiti Teknologi MARA commenced upon receiving the directives from the Faculty of Civil Engineering, UiTM Malaysia. One of the OBE concepts in OBE-curriculum is the programme outcome assessment and evaluation. The Civil Engineering diploma programmes has gone through the assessment programme for their first graduates in June 2009. However. the actual process of this assessment had started in 2007. The assessment and evaluation were done manually by distributing questionnaires to graduating students. However, this method has created problems that are related to time, resources and cost. Not only this process took about two months to produce results, but the process of gathering the data, analysing the data and producing the results has proven to be tedious. The logistic aspect also contributes to the difficulties in carrying out this bi-annual assessment for all campuses in the country. At present, the Faculty of Civil Engineering is the only faculty involved with the exercise. Current development shows that, other faculties will implement the OBE curricular in 2010. Thus, the assessment will be done in a larger scale and may result in complexities. Notwithstanding the complexity of the process, the assessment and evaluation need to be carried out as evidences have to be documented for accreditation purposes. Thus, a more systematic method of assessing and evaluating needs to be developed. This innovation proposes an electronic solution for programme outcome assessment to support the requirement needed in OBE implementation. The system can help in managing data and minimising the use of resources such as paper and support staff for data entry and analysis. It is also able to provide sufficient, reliable and fast results which can be used as performance criteria at the continual quality improvement (CQI) level.